Digital Transformation of Contract Law: Legal Certainty and Human Rights Protection in AI-Based Contracts - Ery Agus Priyono; Olawale Olufemi Akinrinde; Muhammad Najiib Al Fithri; Muhamad Azhar (Universitas Negeri Surabaya, 2026)
The development of artificial intelligence (AI) has driven the digital transformation of electronic contracting practices by introducing automated systems and electronic agents. However, using AI to form and execute contracts raises legal issues, particularly regarding the validity of agreements, legal certainty, and the protection of human rights. According to Indonesian contract law, agreements are valid if they meet the requirements of Article 1320 of the Civil Code (KUHPerdata) which includes mutual agreement and legal capacity. However, AI lacks free will and legal status. This study aims to analyze the discrepancy between applicable legal norms and the practice of using AI in electronic contracts in Indonesia. This study employs normative legal research with a legislative and comparative law approach, focusing on the UNCITRAL Model Law on Electronic Commerce and the United Nations Convention on the Use of Electronic Communications in International Contracts. The results reveal that Indonesian positive law does not explicitly regulate the validity or legal liability of AI-based contracts. This lack of regulation has the potential to cause legal uncertainty and substantive injustice. Therefore, it is necessary to harmonize national law with international standards and integrate a human rights–based approach to ensure legal certainty and justice in AI-based contracts.